DISTRIBUTION OF JAGUAR Panthera onca IN PERU - MAFFEI, Leonardo (2022)
The jaguar (Panthera onca), is the largest feline in America and is threatened by factors such as deforestation, hunting, reduction of its prey and the trafficking of its parts. Therefore, several efforts have been made to conserve this species on a continental level, however, these valuable initiatives have many mapping inaccuracies and exclude important areas for jaguar range. Due this, based on forest and non-forest maps and jaguar observation points in the last 20 years, we present a proposal of maps of current, probable and historical distribution for the jaguar, with areas that cover between 60 and 47% of the surface of Peru.